Problem-based learning for developing interpersonal skills: the case of hospitality and tourism students - Silva, Susana (2022)
Considering that one of the main goals of higher education is to promote the development of employability skills in students so that they can be able to adapt and function in unknown and ever-changing professional contexts, the dichotomy between work and professional practice assumes great relevance. As the tourism industry is constantly changing, a focus on predominantly theoretical training has proven to be insufficient. Several studies have shown that there is a gap between the classroom context and the challenges existing in the real work context. The pedagogical strategies adopted in higher education in Tourism and Hospitality courses continue to show little investment in the development of practical knowledge, skills, and attitudes. In this sense, the use of problem-based learning (PBL) in higher education, as a constructivist strategy, assumes a crucial role. By promoting self-learning, PBL enables the development of conceptual and procedural knowledge, problem-solving skills, critical thinking, creativity, and teamwork skills, thus enhancing motivation and the perception of self-fulfillment. In a PBL setting, students are encouraged to share their opinions, perceptions, and knowledge and to formulate new ideas and concepts. By assuming an active role in the construction of their knowledge, through confrontation with "real situations" and based on a collaborative environment, students develop more meaningful learning, access and use specific skills in meaningful contexts, develop a greater perception of self-confidence and self-efficacy before entering the labor market. By developing a better understanding of the complexities inherent in the real world, they foster their future employability. Considering the challenges faced by hospitality and tourism students in the organizational context, especially when they are responsible for managing people, we used the PBL strategy in the classroom context. Our main research aim is to understand the students' perception of the impact of the use of PBL on the development of skills that enhance their interpersonal skills and employability. The research used a quantitative approach with two evaluation moments: at the beginning of the semester (M1) and at the end of the semester (M2). The data were collected through an online questionnaire during March 2020 and June 2020. We obtained 180 answers for M1 and 165 for M2. The results suggested that, for moment 1, students valued equally all the interpersonal skills, and they intend to develop mostly communication skills. For moment 2, the students valued more all the interpersonal skills. They had considered that the PBL strategy was important to develop their self-confidence and relations with others and less important for initiative and openness. Moreover, the students had considered that this is a very positive strategy to develop the skills in the curricular unit. Our results suggested that the use of problem-based learning for classes that aim to develop practical skills, namely interpersonal skills, should be adopted.